Age-Related Change of Axial Length, Spherical Equivalent, and Prevalence of Myopia and High Myopia in School-Age Children in Shanghai: 2014–2018 - Tao Li; Bo Jiang; Xiaodong Zhou (Journal of Ophthalmology)
Purpose. To investigate the age-related change of axial length (AL), spherical equivalent (SE), and prevalence of myopia and high myopia in children at 7–18-year-olds in Shanghai in 2014 and 2018, respectively. Methods. This was an observational study in Shanghai. The same 3 schools were selected in 2014 and 2018, respectively. AL, SE, prevalence of myopia and high myopia, height, and weight were measured. A questionnaire regarding the lifestyles was completed. Results. Mean age was smaller in 2018 than in 2014 (P<0.001), and mean AL was shorter in 2018 than in 2014 (P=0.003), whereas mean SE was greater in 2018 than in 2014 (P<0.001). The prevalence of myopia and high myopia was lower in 2018 than in 2014 (P<0.001 and P=0.013, respectively). Mean AL increased with age from 7-year-olds to 18-year-olds in 2014 and 2018 (both P<0.001), respectively. Mean SE decreased with age in 2014 and 2018 (both P<0.001), respectively. The prevalence of myopia and high myopia increased with age in 2014 and 2018 (all P<0.001), respectively. Less mean time outdoors and more mean time of study of all children were observed in 2018 than in 2014 (P=0.018 and P<0.001, respectively). Conclusion. This study shows normative growth values for AL and SE in Shanghai children at the age of 7–18-year-olds, as well as the age-specific prevalence of myopia and high myopia.